Relationship between Y Balance Test Scores and Body Composition of High School Female Athletes - ITO, Riyaka; ISHIZUKA, Mizuki; URATA, Ryunosuke; TODA, Mika; ISHIZAKA, Masahiro; IGAWA, Tatsuya; ITO, Shomaru; TAKAHASHI, Hiroto; KIKUCHI, Hinako; SUZUKI, Kosuke; MATSUMOTO, Chiaki (Rigaku ryoho kagaku, 2025)
[Purpose] This study examined the relationship between Y Balance Test (YBT) scores and the body composition of high school female athletes. [Participants and Methods] Thirty-one athletes were classified into two groups based on anterior reach asymmetry (>4 cm or ≤4 cm). YBT scores and body composition, including phase angle (PhA), were assessed and analyzed. [Results] The asymmetry group showed significantly higher BMI, fat mass index, lower-limb muscle mass, and PhA. PhA positively correlated with body weight and muscle mass but negatively with anterior reach distance. [Conclusion] These findings suggest the necessity of evaluating body composition parameters related to the balance ability and injury risk of female high school athletes.